Intramural Ventricular Septal Defect - Saedi, Sedigheh; Parsaee, Mozhgan (International Journal of Cardiovascular Practice, 2017)
Intramural ventricular septal defects (VSDs) are less frequently encountered but clinically significant type of residual interventricular communications seen after complex congenital heart surgeries. Hemodynamically significant intramural VSDs can lead to higher postoperative morbidity and mortality. This case highlights the clinical challenges including the need multiple interventions faced in affected patients.